Effects of Culture on the Credibility of Robot Speech: A Comparison between English and Arabic - Andrist, Sean; Ziadee, Micheline; Boukaram, Halim; Mutlu, Bilge; Sakr, Majd (Tenth Annual ACM/IEEE International Conference on Human-Robot Interaction (HRI ’15), 2015)
As social robots begin to enter our lives as providers of information, assistance, companionship, and motivation, it becomes increasingly important that these robots are capable of interacting effectively with human users across different cultural settings worldwide. A key capability in establishing acceptance and usability is the way in which robots structure their speech to build credibility and express information in a meaningful and persuasive way. Previous work has established that robots can use speech to improve credibility in two ways: expressing practical knowledge and using rhetorical linguistic cues. In this paper, we present two studies that build on prior work to explore the effects of language and cultural context on the credibility of robot speech. In the first study (n=96), we compared the relative effectiveness of knowledge and rhetoric on the credibility of robot speech between Arabic-speaking robots in Lebanon and English-speaking robots in the USA, finding the rhetorical linguistic cues to be more important in Arabic than in English. In the second study (n=32), we compared the effectiveness of credible robot speech between robots speaking either Modern Standard Arabic or the local Arabic dialect, finding the expression of both practical knowledge and rhetorical ability to be most important when using the local dialect. These results reveal nuanced cultural differences in perceptions of robots as credible agents and have important implications for the design of human-robot interactions across Arabic and Western cultures.